2020
DOI: 10.1093/jscr/rjaa153
|View full text |Cite
|
Sign up to set email alerts
|

The use of dorsoradial forearm flap for the treatment of dorsal hand defect

Abstract: Generally dorsal hand defects are often closed with a flap. Dorsoradial forearm artery flap has generally been used in thumb defects; however, it can also be used in the reconstruction of dorsal hand defects thanks to its wide rotation arc and appropriate pedicle length. In this case report, we presented the outcome of a case where the dorsoradial forearm flap was applied to treat the dorsal hand defect. A 27-year-old patient was admitted to emergency room with trauma on hand. Fixation of metacarpal bone fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, techniques to cover hand and forearm soft tissue defects are continuously progressing over time, especially with the development of free flaps and microsurgery. Several studies have reported a satisfactory outcome with utilization of groin flap [ 12 ], paraumbilical flap [ 13 ], Dorsal Intermetacarpal flap [ 14 ], Posterior Interosseus flap [ 15 ], Infraclavicular flap [ 16 ], cross flap [ 17 ], and Chinese Forearm (CFA) flap.…”
Section: Discussionmentioning
confidence: 99%
“…However, techniques to cover hand and forearm soft tissue defects are continuously progressing over time, especially with the development of free flaps and microsurgery. Several studies have reported a satisfactory outcome with utilization of groin flap [ 12 ], paraumbilical flap [ 13 ], Dorsal Intermetacarpal flap [ 14 ], Posterior Interosseus flap [ 15 ], Infraclavicular flap [ 16 ], cross flap [ 17 ], and Chinese Forearm (CFA) flap.…”
Section: Discussionmentioning
confidence: 99%
“…5 In small defects, dorsal rotation flaps, advancement flaps, or hatchet flaps are used. [6][7][8][9][10][11] In moderate defects, cross finger flaps with adipofascial variants are especially used. Immobilization and two-stage operation procedure are important disadvantages in cross finger flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in accordance with the principles of wound repair, adjacent flaps, such as distal radial artery perforator flaps (Karakol et al, 2020), distal ulnar artery perforator flaps (Unal et al, 2011), and dorsal carpal perforator flaps, based on the anterior interosseous artery (Hu, Chen, et al, 2020) may be a better choice. Adjacent flaps (Demiri et al, 2013;Rehim & Chung, 2014) not only have a similar color and texture to the surrounding tissue but also can be completed in the same surgical field, yet it is difficult to suture the donor area directly and often requires skin grafting once the flap width is over 5 cm (Biswas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%